Point-of-care testing of cardiovascular risk factors in Viennese community pharmacies: A cross-sectional study - Thorsten Bischof; Viktoria Mair; Alexander Schmidt-Ilsinger; Philipp Saiko; Susanne Ergott-Badawi; Bernd Jilma; Stefan Deibl; Christian Schoergenhofer (Preventive Medicine Reports)
Objective: Despite being the leading contributor to global mortality, cardiovascular diseases remain undetected in many individuals at-risk. The aim of this study was to evaluate the proportion of individuals with unrecognised cardiovascular risk factors among all-comers in community pharmacies. Methods: This cross-sectional study conducted in 47 Viennese community pharmacies between November 1, and December 31, 2024, screened adults for cardiovascular risk factors using point-of-care testing (HbA1c, lipid profile) and the age-appropriate Systematic Coronary Risk Evaluation 2. An optional follow-up after three months assessed whether medical referral occurred and pharmacotherapy was initiated or changed. Patients treated for diabetes or hyperlipidaemia were excluded. Results: Among 445 individuals, 51 % were identified with increased cardiovascular risk factors. Of these, 151 agreed to participate in the follow-up, in which 66 % were successfully contacted. The respondents reported an attendance rate of 57 % and 43 % received new or modified pharmacotherapy. Conclusions: Community pharmacy-based screening proved effective, identifying numerous previously undiagnosed individuals with increased cardiovascular risk, which is especially remarkable within a comprehensive healthcare system. However, follow-up rates remained low, indicating a gap between risk detection and medical action. A stronger integration of screening interventions with primary care and follow-up pathways with medical institutions may enhance the effectiveness.